The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/sms.14128
|View full text |Cite
|
Sign up to set email alerts
|

Training and development in sport officials: A systematic review

Abstract: Sport officials make significant contributions to organized sport, yet scientific evidence to inform their specialized training and education at various levels has lagged. While psychological and performance demands of expert sport officials have been well documented, the extent of research about talent and expertise development, training efficacy, and broader developmental trajectories is unclear. This systematic review summarizes 30 years of published findings on the study of training and development of spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Physical development and fitness programming for referees remain under-researched topics ( Cunningham, Mergler & Wattie, 2022 ), even though they are of considerable interest to basketball governing bodies and practitioners. Our study revealed that Spanish basketball referees across all competitive levels consistently engage in weekly planned physical activity, with warm-up exercises being a common component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical development and fitness programming for referees remain under-researched topics ( Cunningham, Mergler & Wattie, 2022 ), even though they are of considerable interest to basketball governing bodies and practitioners. Our study revealed that Spanish basketball referees across all competitive levels consistently engage in weekly planned physical activity, with warm-up exercises being a common component.…”
Section: Discussionmentioning
confidence: 99%
“…Referees are essential in maintaining professional sports’ integrity and legitimacy, as they operate in high-pressure environments and are expected to make unbiased judgments ( Cunningham, Mergler & Wattie, 2022 ). This task is particularly challenging for basketball referees, who must make quick and accurate decisions under high-pressure situations ( Karacam & Adiguzel, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, trials of the "IA" court tennis trainer on a larger scale will be conducted for further improvement to become the final product. The results of the study stated that the use of the field tennis trainer model can increase mastery of skills and learning motivation of users/sportsmen, the field tennis trainer model can help athletes in the training process and can facilitate understanding the material well (Cunningham et al, 2022). Beginners, when mastering skills in sports, can increase training time so that beginners are able to master sports skills (Sugihartono, 2019).…”
Section: ) Measurements Expertmentioning
confidence: 99%
“…Their decisions, actions, and communication impact on players' safety, performance, and other match outcomes. Much research has focused on higher order skills and characteristics of elite sport officials, with less also focusing on how to develop, practice, and apply these attributes (Cunningham et al, 2022;Hancock et al, 2021). With an abundance of research into superior performance attributes of athletes and understanding about broad methods to enhance their sport-specific performance skills (Schenk & Miltenberger, 2019), it is only within the past two decades that evidence-based training tools aimed to improve sport official performance have evolved.…”
mentioning
confidence: 99%